Stock option plans for non-executive employees - Core, J (Journal of Financial Economics, 2001)
We examine determinants of non-executive employee stock option holdings, grants, and exercises for 756 firms during 1994–1997. We find that firms use greater stock option compensation when facing capital requirements and financing constraints. Our results are also consistent with firms using options to attract and retain certain types of employees as well as to create incentives to increase firm value. After controlling for economic determinants and stock returns, option exercises are greater (less) when the firm's stock price hits 52-week highs (lows), which confirms in a broad sample the psychological bias documented by Heath et al. (Quarterly Journal of Economics 114 (1999) 601–628).